Appalachia North : A Memoir - Ferrence, Matthew J. (Book collections on Project MUSE., 2019)
"Appalachia North is the first book-length treatment of the cultural position of northern Appalachia--the portion of the official Appalachian Regional Commission zone that lies above the Mason-Dixon line. For Matthew Ferrence this region fits into a tight space of not-quite: not quite "regular" America and not-quite Appalachia. Ferrence's sense of geographic ambiguity is compounded when he learns that his birthplace in western Pennsylvania is technically not a mountain but, instead, a dissected plateau shaped by the slow, deep cuts of erosion. That discovery is followed by the diagnosis of a brain tumor, setting Ferrence on a journey that is part memoir, part exploration of geology and place. Appalachia North is an investigation of how the labels of Appalachia have been drawn and written, and also a reckoning with how a body always in recovery can, like a region viewed always as a site of extraction, find new territories of growth"--